2019
DOI: 10.3390/antiox8120640
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Light on Reactive Oxygen Species and NF-кB in Disease Progression

Abstract: Reactive oxygen species (ROS) are important secondary metabolites that play major roles in signaling pathways, with their levels often used as analytical tools to investigate various cellular scenarios. They potentially damage genetic material and facilitate tumorigenesis by inhibiting certain tumor suppressors. In diabetic conditions, substantial levels of ROS stimulate oxidative stress through specialized precursors and enzymatic activity, while minimum levels are required for proper wound healing. Photobiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 106 publications
(94 reference statements)
0
36
0
3
Order By: Relevance
“…[ 34 ] High levels of ROS inhibit proliferation and reduce cell viability, while low levels of ROS stimulate signaling pathways involved in bone repair. [ 35–37 ] In this scenario, PBM therapy emerges as an alternative therapy to modulate the ROS expression, [ 38 ] and further investigations regarding the ROS modulation in this experimental model are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] High levels of ROS inhibit proliferation and reduce cell viability, while low levels of ROS stimulate signaling pathways involved in bone repair. [ 35–37 ] In this scenario, PBM therapy emerges as an alternative therapy to modulate the ROS expression, [ 38 ] and further investigations regarding the ROS modulation in this experimental model are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using PBM treatment for trauma and injury have shown that PBM decreases the activation of NF-kB (Rizzi et al 2006;Lee et al 2018). However, it is also postulated that ROS and NO generated by PBM treatment trigger the activation of NF-kB (Chen et al 2011;Kumar et al 2019). NO generation is hypothesized to occur when PBM activates CCO by displacement of NO, which generally inhibits CCO (Hamblin 2016).…”
Section: Pbm Treatment Activates a Multidimensional Stressmentioning
confidence: 99%
“…For instance, one of the proteins found to be activated by PBM in neurodegeneration models is the Rac1 GTPase (Song et al 2012;Meng et al 2013), a protein essential for axonal growth, stability, and phagocytosis. Rac1 inhibition causes actin dysfunction and motor neuron degeneration, but over-activation can cause the production of NOX-mediated ROS (D'Ambrosi et al 2014), triggering NF-kB (Chen et al 2011;Kumar et al 2019), causing the production and release of pro-inflammatory cytokines and oxidative stress (Liu et al 2017). Hence, the activation of Rac1 can either alleviate or exacerbate neurodegenerative disease conditions.…”
Section: Pbm Influences An Interconnected Network Of Cellular Signalimentioning
confidence: 99%
“…PBM therapy and PBM has been shown to affect inflammation, inflammatory markers and cytokine production, and oxidative stress [ 24 27 ]. In the present study, we investigated the levels of cox-2, IL-6, and TNF- α postirradiation at 660 nm in diabetic wounded fibroblast cell culture models.…”
Section: Introductionmentioning
confidence: 99%